SERMON RHETORIC PATTERNS OF PRESIDENT JOKO WIDODO’S ORATION IN THE OCCASION OF BUNG KARNO'S ORATION ON JUNE 1, 1945 COMMEMORATION - Noermanzah Noermanzah (Universitas Sembilanbelas November Kolaka, 2016)
This study aims to provide an understanding of the pattern of sermon rhetoric oration of President Joko Widodo in Commemoration of Bung Karno's oration June 1, 1945 in Bandung, West Java on Wednesday, June 1, 2016. This study used qualitative methods with data collection technique using the documentation. Data were analyzed using content analysis with the steps: identify, review of the literature, define, data collection, data analysis, interpretation, Dissemination of results. The results of this study indicate that the pattern of rhetoric using a model of sermon on the oration of President Joko Widodo in Commemoration of Bung Karno's oration June 1, 1945 in Bandung, West Java on Wednesday, June 1, 2016, namely the introduction or preface (introduction), trunk (body), and conclusion.